Experimental infection of cattle with wild type peste-des-petits-ruminants virus – Their role in its maintenance and spread. (June 2019) - Couacy-Hymann, Emmanuel; Koffi, Mathurin Y.; Kouadio, Valère K.; Mossoum, Arsène; Kouadio, Léonce; Kouassi, Antonette; Assemian, Krou; Godji, Privat H.; Nana, Pauline
Summary: Peste des petits ruminants (PPR) is a major Transboundary animal disease (TADs) of sheep and goats in tropical regions caused by PPRV which can also infect cattle without any clinical signs but inducing seroconversion. However the epidemiological role of cattle in the maintenance and spread of the disease is not known. For the purposes of the present study, cattle were infected with a wild type candidate from each of the four lineages of PPRV and placed in separate boxes. Naive goats were then introduced into each specific box for the 30 days duration of the experiment. The results showed that no clinical signs of PPR were recorded in these infected cattle nor in the in-contact goats. The nasal and oral swabs remained negative. Serum from animals infected with three (3) of the wild type isolates of PPRV showed high percentage inhibition (PI % > 65%) in a cELISA. Only two animals out of three infected with the Nigeria 75/3 strain of lineage 2 (mild strain) had specific anti-PPR antibodies but with PI% values around the threshold of the test. Our findings suggest that cattle are dead-end hosts for PPRV and do not play an epidemiological role in the maintenance and spread of PPRV. In a PPR surveillance programme, cattle can serve as indicators of PPRV infection. Highlights: PPRV infects both small ruminants and cattle with no clinical signs in the latest specie. Infection of cattle with wild type PPRV of each of the four lineages induces production of specific antibodies against PPRV. Cattle infected with PPRV did not excrete the virus and in-contact susceptible goats and sheep remain seronegative. Absence of viral excretion is confirmed by negative results on oral and nasal swabs from infected cattle Cattle are dead end hosts for PPRV and do not play an epidemiological role in the maintenance and spread of PPRV.